Measles: reemerging threat of epidemic in peru - Loayza-Alarico, Manuel J. (2019)
Measles, considered one of the most contagious transmissible infections due to its high potential epidemic risk of transmission, remains a focus of concern in the world due to the increase in cases and its consequent morbidity and mortality. The rash usually starts on the face, and in a centrifugal way it spreads to the trunk and extremities. Although the disease determines a strong humoral and cellular immune response stimulating specific immunity for life, it produces at the same time an important immunosuppression that lasts several weeks increasing the susceptibility to secondary infections. Measles was considered eliminated from the Americas since 2002 because to the absence of endemic transmission of the disease in the region; achievement achieved by regional efforts to achieve high vaccination coverage through regular immunization programs and mass vaccination campaigns. However, until April 2019 the Pan American Health Office reported that 12 countries reported confirmed cases: Argentina, Bahamas, Brazil, Canada, Chile, Colombia, Costa Rica, United States of America, Mexico, Peru, Uruguay and Venezuela. 09 countries reported cases imported from countries outside the Region with different genotypes. Also, between January 1 and April 11, 2019, 5556 cases of measles were confirmed in 20 States of the United States.